Superposed Epoch Analyses of Geoelectric Field Disturbances in Japan in Response to Different Geomagnetic Activities - T. Zhang; Y. Ebihara (Space Weather)
Abstract An increase in geomagnetically induced currents (GICs) is an inevitable result of geomagnetic field disturbances, and is harmful to the power grid, in particular, at high latitudes. At mid and low latitudes, the amplitude of the GICs is, in general, small, but large‐amplitude GICs are often observed during magnetic storms. It is of importance to understand major characteristics and extreme values of GICs at mid and low latitudes. For the geoelectric field disturbances ΔE observed at Kakioka (27.8° geomagnetic latitude) in Japan in 1996–2004, we performed superposed epoch analyses with respect to three types of geomagnetic disturbances: (a) storm sudden commencements (SSCs)/sudden impulses (SIs), (b) main phase of magnetic storms, and (c) bay disturbances. It is shown that the SSCs/SIs and the main phase of the magnetic storms are equally important for causing large‐amplitude disturbances of ΔE at Kakioka. GICs are thought to be amplified when the SIs and/or the bay disturbances occur during the magnetic storms. The maximum value of ΔE tends to be correlated with the maximum value of ΔH during the three types of events, where ΔH is the horizontal component of the geomagnetic field. Assuming that a quasi‐linear relationship between the maximum ΔE and the maximum ΔH is valid, we estimated GICs at three substations in Japan for an extreme SSCs/SIs, and the extreme magnetic storms. This scheme could be applicable to estimate roughly the GICs against extreme events, and to forecast the maximum GICs in a real‐time manner.